Analisis Hasil Belajar Permainan Bulu Tangkis Pada Pembelajaran Pjok Siswa Kelas VIII SMP Negeri Satap Tandassura - Suwardi, Suwardi; Badaru, Benny; Yusnadi, Yusnadi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
The game of badminton in the Tandassura Polman Mandar area is well known by the wider community and in schools, including students at the Tandassura Polewali Mandar State Middle School, but its development has not shown adequate which can be used for the learning process. Teaching and practicing, especially for class VIII students, is also explicitly stated in the curriculum as a mandatory subject to be studied, so that it really supports the smooth running of learning, especially the badminton games held by the physical education teacher at this school. Thus, how good the results of learning the game of badminton achieved by students are. So research was carried out aimed at finding out the level of students' badminton learning achievement. The population of this study was all 28 students in class VIII of Satap Tandassura Polewali Mandar State Middle School. This type of research is quantitative descriptive. Methods for collecting interview data and documenting the learning outcomes of each student from the physical education teacher at the school. Data analysis uses descriptive percentage techniques. From the results of statistical data analysis, it was found that 8 students (28.6%) were in the "very good" category, 20 students (71.4%) were in the "good" category, and there were no students in the "fair," "poor," and "very good" categories. not enough". Conclusion: The results of badminton learning for students at SMP Negeri Satap Tandassura Polewali Mandar are categorized as "Good.".